Reliability of chest pain risk scores in cancer patients with suspected acute coronary syndrome - Alyeşil, Cansu (Clin Exp Emerg Med, 2020)
OBJECTIVE: The history, electrocardiogram, age, risk factors, troponin (HEART), the thrombolysis in myocardial infarction (TIMI), and Global Registry of Acute Coronary Events (GRACE) scores are useful risk stratification tools in the emergency department (ED). However, the accuracy of these scores in the cancer population is not well known. This study aimed to compare the performance of cardiac risk stratification scores in cancer patients with suspected acute coronary syndrome (ACS) in the ED. METHODS: This prospective cohort study recruited patients with cancer who visited the ED because of suspected ACS. The development of any major adverse cardiac events (MACE) within 6 weeks was recorded, with the study outcome being a MACE within 6 weeks of ED admission. RESULTS: A total of 178 patients participated in this study, of whom 5.6% developed a MACE. Statistically significant differences were found between the mean HEART and TIMI scores in predicting MACE. The HEART score had the highest area under the curve (0.64; 95% confidence interval, 0.48–0.81), highest sensitivity (80%), and highest negative predictive value (97.5) in patients with cancer. CONCLUSION: We found a similar rate of MACE in cancer patients with low-risk chest pain compared to that in the general population. However, the HEART, TIMI, and GRACE scores had a lower performance in cancer patients with MACE compared to that in the general population.